(Un)seeing like a prison: Counter-visual ethnography of the carceral state. (May 2014) - Schept, Judah
While prisons proliferate in the rural landscape and sites of penal tourism expand, the carceral state structures the available visual and analytic vantages through which to perceive this growing visibility. Using examples from fieldwork in Kentucky, including Appalachian prison communities and a site of penal tourism, this article proposes 'counter-visual' ethnography to better perceive the ideological work that the carceral state performs in the spatial and cultural landscape. A counter-visual ethnography retrains our eyes to see that which is not 'there' but which structures the contemporary empirical realities we observe, record, and analyze: the ghosts of racialized regimes past, the sediment of dirty industry that seeps into and imbues the present, and the trans-historical and trans-local circulation of carceral logics and epistemologies. In addition, this article suggests the important role images play in shaping alternative vantages from which to better perceive the carceral state with historical, spatial, and political acuity.